High performance MoS2-based field-effect transistor enabled by hydrazine doping. (21st April 2016) - Lim, Dongsuk; Kannan, E S; Lee, Inyeal; Rathi, Servin; Li, Lijun; Lee, Yoontae; Khan, Muhammad Atif; Kang, Moonshik; Park, Jinwoo; Kim, Gil-Ho
Abstract: We investigated the n-type doping effect of hydrazine on the electrical characteristics of a molybdenum disulphide (MoS2 )-based field-effect transistor (FET). The threshold voltage of the MoS2 FET shifted towards more negative values (from −20 to −70 V) on treating with 100% hydrazine solution with the channel current increasing from 0.5 to 25 μ A at zero gate bias. The inverse subthreshold slope decreased sharply on doping, while the ON/OFF ratio increased by a factor of 100. Gate–channel coupling improved with doping, which facilitates the reduction of channel length between the source and drain electrodes without compromising on the transistor performance, making the MoS2 -based FET easily scalable.